PENGARUH MOTIVASI KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA KELURAHAN SUNGI KULON - -, Rizkya Zahli (KINDAI, 2024)
This research aims to identify and analyze the influence of work motivation and organizational commitment on employee performance in an organization. Work motivation and organizational commitment are key factors that can influence employee productivity and contribution in achieving organizational goals. The research method used is a survey method by distributing questionnaires to respondents consisting of employees at various levels in the organization. These findings have the implication that companies need to pay attention to and improve work motivation factors and organizational commitment in an effort to improve employee performance. Measures such as providing training, career development, and promoting organizational commitment policies can be effective strategies to achieve this goal. Apart from that, this research can also be a basis for further research to explore other factors that can influence relationships